Perception of wine labels by Hong Kong Chinese consumers - Vicky Chi Man Tang; Anat Tchetchik; Eli Cohen (Wine Economics and Policy, 2015)
Despite Hong Kong's growing wine consumption and the abundance of retail brands available there, the demanding choice task faced by its wine consumers, who are more subject to a mix of Chinese and Western cultural influences than consumers in other South Asian countries, has not been studied until now. This exploratory study aims to delve into the importance of wine label attributes for Hong Kong Chinese wine consumers, and to shed light on the ways in which their perceptions affect their choice of wine. Employing an online survey, the results suggest that Hong Kong Chinese wine consumers look for the top three most searched attributes: wine origin, grape variety, and food and wine pairing. A simple means differences test indicated that a traditional label design is favored over modern and contemporary wine labels, and that yellow is the most preferred color. However, a data-driven segmentation analysis reveals that about 95% of young Hong Kong Chinese wine consumers prefer "elegant contemporary" labels with red as the dominant color. These findings could be useful for wineries entering this market and for wine label designers who wish to better understand how Hong Kong wine consumers assess alternatives when choosing a bottle of wine.
Keywords: 330; Chinese wine consumers; Extrinsic wine attributes; Hong Kong wine market; Wine label